A Study on the Significance of Indian Insurance Industry and Its Financial Performance: Exploring the Evolution and Regulation of the Indian Insurance Industry (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The insurance industry in India has passed through a period ofstructural changes under the combined impact of financial sector reforms ingeneral and insurance sector in particular. The market for insurance servicespreviously was monopolistic while the market place was regulated and insurancecompanies were expected to receive assured spreads over their costs of fundsand systematic demand for their products. This phase in insurance business wasthe result of sheltered markets and administered prices for various insuranceproducts.